An UHF RFID Reader Antenna with Multitag Identification for Extremely Low-Temperature Medical Systems - Ji S. Jung; Jung N. Lee; Joung M. Kim; Jong K. Park (International Journal of Antennas and Propagation)
A radio frequency identification reader antenna having multitag identification for medical systems is presented, which consists of four PIFAs, two hybrid couplers, and four power dividers. The high isolation is achieved by the symmetric design of the antenna geometry and four power dividers, which are fed by two hybrid couplers. The experimental results show an isolation of more than 40 dB in the North American (902–928 MHz), Korean (917–923.5 MHz), and Japanese (916.7–923.5 MHz) RFID frequency bands.